2022
DOI: 10.1109/access.2021.3135467
|View full text |Cite
|
Sign up to set email alerts
|

Transformer Fault Diagnosis Based on Multi-Class AdaBoost Algorithm

Abstract: Traditional shallow machine learning algorithms cannot effectively explore the relationship between the fault data of oil-immersed transformers, resulting in low fault diagnosis accuracy. This paper proposes a transformer fault diagnosis method based on Multi-class AdaBoost Algorithms in response to this problem. First, the AdaBoost algorithm is combined with Support Vector Machines (SVM), The SVM is enhanced through the AdaBoost algorithm, and the transformer fault data is deeply explored. Then the dynamic we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Although SVM has been widely used in transformer fault diagnosis, study has shown that a single SVM is inferior to some ensemble learning methods [23,12,[24][25][26]. Wang et al [23] proposed a transformer fault diagnosis method based on Bayesian optimization random forest, compared with a single intelligent diagnosis method, it has a higher accuracy rate.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although SVM has been widely used in transformer fault diagnosis, study has shown that a single SVM is inferior to some ensemble learning methods [23,12,[24][25][26]. Wang et al [23] proposed a transformer fault diagnosis method based on Bayesian optimization random forest, compared with a single intelligent diagnosis method, it has a higher accuracy rate.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [23] proposed a transformer fault diagnosis method based on Bayesian optimization random forest, compared with a single intelligent diagnosis method, it has a higher accuracy rate. Another example is boosting ensemble learning algorithm, Liu et al [24] proposed a AdaBoost-RBF method, the accuracy of fault diagnosis can be effectively improved through boosting ensemble method. There is also PSO-ELM-Adaboost [25] and Adaboost-cloud [26] transformer ensemble learning fault diagnosis method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The performance of SVM mainly depends on the selection of kernel function and parameters; therefore, it motivates many scholars to use other intelligent algorithms to optimize the hyperparameters of SVM for the sake of achieving better classification results, such as particle swarm optimization [84], Krill Herd algorithm [92] and other methods [90]. Jifang et al [93] enhanced the SVM by applying the AdaBoost algorithm to deeply explore the transformer fault data. Moreover, improved particle swarm optimization algorithm (IPSO) is used to optimize the parameters of the SVM.…”
Section: Fault Diagnosis Of Transformermentioning
confidence: 99%